Recurrent Acute Rheumatic Fever with Severe Rheumatic Mitral Stenosis in 11-years-old Patient: A Case Report - Kino, Kino; Hariyanto, Didik; Fernando, Harben; Risani, Puti (Frontiers on Healthcare Research, 2026)
Background: Acute Rheumatic Fever (ARF) was an immune-mediated complication of Group A Streptococcus (GAS) infection that could progress to Rheumatic Heart Disease (RHD) through repeated or untreated episodes. While RHD typically developed over years, yet some children in endemic settings can develop severe multivalvular disease rapidly, likely due to unrecognized/subclinical ARF and inadequate secondary prophylaxis. This case adds to the literature by illustrating severe rheumatic mitral stenosis at a young age with clinical features suggestive of recurrent ARF despite no documented prior ARF, emphasizing rapid progression could occur in endemic settings. Case report: An 11-year-old male presented with exertional dyspnea and intermittent joint pain without swelling or redness. There was no previously documented ARF episode. Serology showed positive anti-streptolysin O (ASO) supporting recent streptococcal exposure. Echocardiography demonstrated severe mitral stenosis, moderate mitral regurgitation, moderate aortic regurgitation, moderate aortic stenosis, and severe tricuspid regurgitation with high probability of pulmonary hypertension. Diagnosis of recurrent ARF with severe RHD was established using the modified Jones criteria, supported by echocardiographic evidence of multivalvular involvement. Initial management was adjusted for penicillin allergy and included azithromycin, corticosteroids, beta-blockers, diuretics, and nutritional rehabilitation, followed by erythromycin for secondary prophylaxis. Conclusion: This case highlighted the possibility of rapid progression to severe RHD in children due to subclinical ARF. Early diagnosis, routine echocardiography, strict adherence to secondary prophylaxis, and patient education were vital to prevent long-term complications, including heart failure and surgical interventions.